Kolonialisme Belanda di Wilayah Kecamatan Parlilitan dan Dampaknya terhadap Sosial-Budaya Masyarakat, 1877-1907 - Herrio Tekdi Nainggolan (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
This paper analyzes the Dutch colonial presence in the Parlilitan District between 1877 and 1907, examining its impact on the socio-cultural dynamics of the local community. Historical records indicate that Dutch colonialism in the Batak region—particularly in Parlilitan—was not only exploitative but also constituted a form of systemic violence and a violation of human rights. Employing qualitative research methods, including interviews and literature review, this study reveals that the Dutch regime engaged in coercive and oppressive practices that instilled fear among the local population. These included threats, forced labor (rodi), and the destruction of community assets such as rice field huts. Direct resistance was rare, as the colonial forces possessed superior weaponry and physical strength. Instead, the local population resorted to passive forms of resistance, such as fleeing into forests or migrating to safer regions. The colonial period significantly altered the community’s socio-cultural fabric, resulting in a collective sense of inferiority, the erosion of customary legal authority, transformations in labor patterns, and increased mobility due to the construction of transportation infrastructure.